Hubungan Pemberian Asupan Makanan Pendamping Asi (MPASI) Dengan Pertumbuhan Bayi Atau Anak Usia 6-24 Bulan - Alfie Ardiana Sari; Ratih Kumorojati (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: Relationship Of Complementary Food Intake Of Breast Milk (MPASI) With Baby / Children Growth Ages 6-24 Months The first two years of life is a period that lasts very short and cannot be repeated again, so it is referred to as a "golden period" or a window of opportunity. Inappropriate nutritional intake will also cause children to experience malnutrition, which ultimately increases the incidence of morbidity and mortality. According to a survey of micronutrients in 12 provinces in Indonesia shows that the age group 6-11 months consume nutrients lower than other age group. Purpose of this research is the relationship of Complementary Food Intake of Breast Milk (MPASI) with infants / children growth ages 6-24 months. This study was a descriptive analytic study with a cross-sectional approach. The population is mothers who have babies / children aged 6-24 months. Samples were taken by consecutive sampling method with 18 babies / children. Data analysis using Chi Square with a significance limit of α = 0.05. Respondents with Complementary Food Intake of Breast Milk giving, most of the growth was normal, namely 10 respondents (55.5%), respondents with sufficient Complementary Food Intake of Breast Milk giving, normal growth was 2 respondents (11.1%) and respondents with less Complementary Food Intake of Breast Milk giving were high growth (11.1 %). There was no significant relationship between the provision of complementary feeding and the growth of infants / children 6-24 months in the Gamping Wirastri Integrated Health Center in Sleman.